2022
DOI: 10.3390/jpm12020161
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Manual Method versus an Automated, Probability-Based Algorithm to Identify Patients at High Risk for Pharmacogenomic Adverse Drug Outcomes in a University-Based Health Insurance Program

Abstract: We compared patient cohorts selected for pharmacogenomic testing using a manual method or automated algorithm in a university-based health insurance network. The medication list was compiled from claims data during 4th quarter 2018. The manual method selected patients by number of medications by the health system’s list of medications for pharmacogenomic testing. The automated method used YouScript’s pharmacogenetic interaction probability (PIP) algorithm to select patients based on the probability that testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…9 Several implementation studies on pharmacogenetic testing have been conducted, 8,[10][11][12][13][14][15] and some specifically for psychiatric medications. [16][17][18][19][20] While prescribers have begun to use pharmacogenetic testing in routine care in different specialties, widespread adoption has lagged both across and within institutions: analysis of administrative claims for Medicare and Medicaid in one US state found that only 4.4% of Medicaid beneficiaries and 10.5% of Medicare beneficiaries who had begun a prescription of a medication included in the FDA table of drugs with pharmacogenetic testing information on the label actually received pharmacogenetic testing. 21 Prior work has shown that a multitude of factors, from individual prescriber to larger structural issues, are barriers to pharmacogenetic testing adoption.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Several implementation studies on pharmacogenetic testing have been conducted, 8,[10][11][12][13][14][15] and some specifically for psychiatric medications. [16][17][18][19][20] While prescribers have begun to use pharmacogenetic testing in routine care in different specialties, widespread adoption has lagged both across and within institutions: analysis of administrative claims for Medicare and Medicaid in one US state found that only 4.4% of Medicaid beneficiaries and 10.5% of Medicare beneficiaries who had begun a prescription of a medication included in the FDA table of drugs with pharmacogenetic testing information on the label actually received pharmacogenetic testing. 21 Prior work has shown that a multitude of factors, from individual prescriber to larger structural issues, are barriers to pharmacogenetic testing adoption.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…However, realizing benefits from pharmacogenetic testing in real‐world practice will depend on the extent to which prescribers value and use it 9 . Several implementation studies on pharmacogenetic testing have been conducted, 8,10–15 and some specifically for psychiatric medications 16–20 . While prescribers have begun to use pharmacogenetic testing in routine care in different specialties, widespread adoption has lagged both across and within institutions: analysis of administrative claims for Medicare and Medicaid in one US state found that only 4.4% of Medicaid beneficiaries and 10.5% of Medicare beneficiaries who had begun a prescription of a medication included in the FDA table of drugs with pharmacogenetic testing information on the label actually received pharmacogenetic testing 21 .…”
Section: Introductionmentioning
confidence: 99%